THE FORMATION OF THE GREEN BUILDING MARKET OF THE RUSSIAN CITIES - Pahomova, Ekatarina Gennadievna; Tomakov, Vladimir Ivanovich; Tomakov, Maksim Vladimirovich (Journal of Applied Engineering Science, 2017)
The article discusses basic directions of construction sector development in modern ecological conditions, principles of sustainable development of cities and the problems hindering implementation of green building principles in the Russian Federation. The article indicates the most promising concept of a building complex development which is the construction in compliance with environmental standards (green building). The peculiarities of green building in Russia are considered and the reasons for its slow development are revealed. The reasons hindering large-scale application of green construction standards are discussed. The methods of the government incentives for green technologies market in Russia are proposed.